Association of Patient Characteristics and Polypharmacy with the Potential for Drug Interactions among Hypertensive Patients at Bakunase Community Health Center - Tanggung, Agatha Febryani Charmy; Riwu, Magdarita; Purnasari, Cahyani; Syahrir, Syahrir (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chronic hypertension frequently has comorbidities, necessitating the use of several drugs (polypharmacy), which raises the possibility of drug interactions. This study aimed to determine the prevalence of polypharmacy, potential drug interactions, and the association between patient characteristics, polypharmacy, and potential drug interactions among hypertensive patients at Bakunase Primary Health Center. 572 hypertensive patients' medical data from January to December 2025 were used in this analytical observational study, which used a retrospective cross-sectional approach. Drugs.com® and Medscape® were used to identify potential drug interactions, and the Chi-square test was used to evaluate the results. According to the findings, 32.3% of patients had polypharmacy and 63.7% of patients had possible drug interactions. While polypharmacy was substantially linked to possible drug interactions (p = 0.001), age was significantly linked to both polypharmacy and potential drug interactions (p = 0.003). We conclude that among hypertension patients, age and polypharmacy are strongly linked to a higher likelihood of possible medication interactions.